ARKETIPE TOKOH UTAMA DALAM NOVEL MAHIKA KARYA AYA: KAJIAN PSIKOLOGI ANALITIK CARL GUSTAV JUNG - Evitriana Anggraeni; Dicky Rachmat Pauji; Iskandarsyah Siregar (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2023)
This study aims to identify and classify categories of personality archetypes and to analyze the layers of personality archetypes found and described in the main characters in Mahika novel by Aya. The theory used in this study is Carl Gustav Jung's analytic psychology theory to understand several layers of personality archetypes using the descriptive qualitative method. The data source used is Mahika novel by Aya in the form of narrative texts and character dialogues that describe the personality archetypes of the main characters. The data were obtained using library techniques, reading, and taking notes. The results of the study show that four layers of personality archetypes are reflected in the characters Dara, Aksa, and Deehan as the main characters in the novel. The archetypes include persona, shadow, anima or animus, and the self.